AB0323 Patients with Higher Education Present Greater Improvements on Functional Status in Early Rheumatoid Arthritis. (9th June 2015) - Jiang, X.; Sandberg, M.; Saevarsdottir, S.; Klareskog, L.; Alfredsson, L.; Bengtsson, C.
Abstract : Background: Low socioeconomic status (SES), measured through a variety of ways (e.g. formal education, occupation, household income, ethnicity) has been associated with an increased risk of rheumatoid arthritis (RA), an elevated economic burden for patients and society, as well as a worse disease outcome. Objectives: To investigate the effect of educational status (achieving a university/college degree) on the prognosis of RA overall, as well as on disease subsets based on ACPAs, in terms of DAS28, physician assessment, VAS-pain, and HAQ. Methods: We used cases from the population-based EIRA study with outcomes followed-up in the Swedish Rheumatology Quality Register (N=3021). We categorized the outcomes in different ways: 1) having equal to/above vs. below median levels; 2) achieving low disease activity, good response, and remission vs. not achieving; 3) having scores decreased over the median vs. less than median. We calculated the ORs of those outcome categories as an effect of higher education, both at diagnosis and for the first three follow-up visits (3, 6, 12 months). Results: We found patients of higher education initiated with less pain and less functional disability (VAS-pain: 49 (28-67) vs. 53 (33-71), p<0.0001, HAQ: 0.88 (0.50-1.38) vs. 1.00 (0.63-1.50), p=0.001). The effects persisted across the follow-up period. They had greater chances to achieve pain remission (3-month-visit: 1.35 (1.08-1.69); 6-month-visit: 1.22 (0.95-1.56); 1-year-visit: 1.23 (1.00-1.52)) and improve to a larger extent (HAQ decrease over the median: 3-month-visit: 1.45 (1.13-1.86); 6-month-visit: 1.41 (1.07-1.86); 1-year-visit: 1.43 (1.12-1.82)). Conclusions: Higher educated patients experienced less pain and less functional disability starting from baseline throughout the first year receiving standard care; they achieved pain remission more and attain greater improvements on physical function as compared to less educated patients. We could not identify any distinct effects of educational background on disease activity related outcomes. Disclosure of Interest: None declared